RTHP-09. SINGLE INSTITUTION'S EXPERIENCE FOR PEDIATRIC INTRACRANIAL EPENDYMOMA TREATED WITH ADJUVANT RADIOTHERAPY. (11th November 2019) - Lee, Joongyo; Hee Choi, Seo; In Yoon, Hong; Woo Han, Jeong; Lee, Ikjae; seok Kim, Dong; Suh, Chang-Ok
Abstract: PURPOSE: To investigate long term outcomes of pediatric intracranial ependymoma treated with maximal safe resection followed by radiotherapy in single institution. METHODS: Between 1983 and 2016, 42 pediatric patients received adjuvant radiotherapy after surgery. There were 19 and 23 grade II and III ependymomas, and total resection could be performed in 50% of patients. There were 4 patients with initial leptomeningeal seeding, and craniospinal irradiation (CSI) was the component of adjuvant treatment in 5 patients including them. Local radiotherapy (median 54 Gy (range, 45–60 Gy) was performed in all the rest patients excluding three with whole-brain radiotherapy. RESULTS: With a median follow-up of 89 months, 14 patients (33%) experienced recurrences after radiotherapy (m/c: intracranial, 79%, all within tumor bed). The 5- and 10-year progression-free survival (PFS) rates were 70% and 63%, and overall survival (OS) rates were 85% and 78%, respectively. The recurrence rates were significantly higher in patients younger than 3 years (64% vs. 23%, p = 0.024) or with subtotal resection (STR) (52% vs. 15%, p = 0.009). In multivariate analyses, age and STR were significant factors for PFS (p = 0.007 and 0.028, respectively). There was no independent prognostic factor for OS on multi-variate analysis. Fourteen patients experienced recurrence. Among them, all of 6 grade II cases showed local recurrence. Four grade II cases (67%) underwent aggressively salvage treatments such as resection, stereotactic radiosurgery were still under observation. However, 75% of 8 grade III recurrent cases were expired, despite aggressive salvage treatments. All 3 patients with seeding recurrent were grade III and died from disease. CONCLUSION: Local adjuvant radiotherapy showed favorable survival in pediatric ependymoma. Even if recurrence occurs, aggressive salvage treatment would be needed for grade II ependymoma.